Manajemen Strategik Kepala Sekolah Dengan Menerapkan Media Pembelajaran Serbaneka Untuk Meningkatkan Minat Belajar Siswa (Studi Smp Muhammadiyah 25 Rantau Prapat) - Hidayati Hidayati; Elfrianto Elfrianto; Salim Aktar (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2023)
The focus of this research is how the principal's strategy in increasing student interest in learning and school students (SMP Muhammadiyah 25 Rantauprapat. overcome the things that cause low learning interest of students and schoolgirls (Study of SMP Muhammadiyah 25 Rantauprapat).The principal's strategic management in achieving school effectiveness is to increase student interest in learning, one of which is by using teaching tools or methods that are in accordance with the material provided. taught to students. Various learning media is one of the factors from outside students (external) that affects student learning interest. The research method used in this study is a qualitative research approach. The data collection technique used by the researcher is through observation and wawa how to source the object to be studied. The subject of this research is students externally, while the object of this research is SMP Muhammadiyah 25 Rantauprapat. The sources of this research data will be obtained through documents or archives, sources (informants), events or activities, places or locations, objects and pictures contained in the research place or location. The results of this research activity showed that students' interest in learning was low when the teacher used the learning media of lectures and notes in delivering learning material, there was no interest and interest and a sense of liking when students took part in the learning process in the classroom. But when the teacher applies various learning media, student interest in learning is greatly increased. Various learning media are learning media that can take advantage of the existing potential of an area around the location, or around the school